1985
DOI: 10.1002/sim.4780040104
|View full text |Cite
|
Sign up to set email alerts
|

A community trial strategy for evaluating treatment for symptomatic conditions

Abstract: A method has been developed for simultaneously comparing the usefulness of many treatments of established value for symptomatic medical conditions. Medical assessment of outcome is not employed. Instead patients are required to assess treatments prescribed during the course of ordinary general practice rather than under the strictly controlled settings of most clinical trials. Outcome incorporates patient compliance and treatment acceptability and is based on patients' subjective judgments of the usefulness of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1986
1986
2004
2004

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Measures of outcome on BDP were compared with those on AST using tests for paired data. The significance of differences on analogue line scores was assessed using the paired /-test, since previous studies have shown parametric tests to be the most appropriate for these scores [10]. The significance of differences for categorical data was assessed using the non-parametric McNemar Test for 2x2 tables or Stuart-Maxwell Test for larger tables.…”
Section: Discussionmentioning
confidence: 99%
“…Measures of outcome on BDP were compared with those on AST using tests for paired data. The significance of differences on analogue line scores was assessed using the paired /-test, since previous studies have shown parametric tests to be the most appropriate for these scores [10]. The significance of differences for categorical data was assessed using the non-parametric McNemar Test for 2x2 tables or Stuart-Maxwell Test for larger tables.…”
Section: Discussionmentioning
confidence: 99%